The medical-scientific discourse on the relationship between epilepsy and work: Prescriptions, limits and possibilities for the subject worker - Golfetto, Vando; Dametto, Jarbas; Moretto, Cleide Fátima (FCL-UNESP Laboratório Editorial, 2020)
This paper attempts to question the concepts related to epilepsy, and in particular, the medical-scientific discourse on the relationship between the disease and work life. A non-exhaustive literature review was used to examine historical and conceptual elements, aiming to identify how epilepsy was conceived in the West until it was understood through scientific knowledge, and how this knowledge mediated the capacitation or disablement of the subject undertaking paid work. When the pre-modern discourse declined, medical science appropriated epilepsy by giving it the status of an organic disease. However, the stigma of epilepsy, previously incited by obscure interpretations, has not been extinguished and it continues to interfere with personal relationships, especially when it is understood that work is a form of social relationship, involving the body and subjectivity. It is noteworthy that technical arguments supported by the perspective of risk and safety generate restrictive prescriptions to working life, while the academic sphere ponders the discourses which aim to preserve personal autonomy for sufferers of epilepsy, and basically these discourses can meet in contemporary times. The Foucaultian assumptions related to such discourses, in the knowledge-power perspective, can increase the lucidity around the effective organic materiality of this illness, emphasizing the discursive apprehension of the phenomenon and its effects.